A criança e a apropriação da cultura escrita: uma possibilidade de alfabetização discursiva - Abreu, Márcia Martins de Oliveira (2019)
This PhD research aimed to develop a methodological possibility of working with children in the process of appropriation of written language, supported by texts constructed and used socially. In order to reach the proposed goal, an intervention research was carried out with a 1st grade class from Elementary School of a federal school system located in the city of Uberlândia / MG, in which the researcher acted concomitantly as a teacher. The proposal was made from Action Plans made up of specific didactic sequences idealized for different textual genres. The organization of all the work was guided by four thematic axes, being: Extratextual context, Graphic text, Word and Reading. The data were generated in the relation between the children and the researcher during the academic year of 2016. The methodological tools were the Plans of action along with the participant observation, the construction of field diary and the transcription of the filming of micro interviews occurred in micro events of the daily with the subjects on the oral and written productions produced in the course of the experiences. The research was based on the theoretical assumptions defended by Bakhtin and Volochinov on language and the Cultural Historical Theory represented especially by Vygotsky, fundamental for guiding the work and the analyzes of the data. For the idealization of the pedagogical proposal of intervention were sources of inspiration Bajard, Jolibert, Schneuwly, Dolz, Marcuschi and Bernardin. For the analysis of data the research was also supported by studies of authors from several areas, among which we can highlight, besides those already mentioned, Arena, Smith, Fiorin and Smolka. The results indicated that the involvement of the subjects in the proposed work with the textual genres, guided by the thematic axes, qualitatively assisted both the literacy process of the students as well as their processes of language and thought development. Thus, the proposal presents itself as a real methodological possibility for the formation of readers and producers of texts.